Students’ perception of WhatsApp usage as an additional learning aid at a Dental College in Pakistan - Afifa Ehsan; Naila Umer; Ali Raza; Maryam Masood; Farhan Riaz; Sana Akram (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: Technological advancements have transformed society into a global entity; medical education is no exception. Innumerable social media platforms such as Facebook, WhatsApp, Instagram, and Edmodo encourage collaborative learning, improved communication, and knowledge-sharing. The current study aims to assess students’ perception of WhatsApp as an additional educational and learning aid for communication purposes, sharing of learning materials, and as a discussion forum. METHODOLOGY: This cross-sectional study was carried out from July 2021 to December 2021 at Faryal Dental College, Sheikhupura, Pakistan. A standardized questionnaire was prepared and circulated amongst students of 1st Year BDS to Final Year BDS. Responses were analyzed using SPSS Version 20. RESULTS: The study comprised 150 participants; the majority, i.e., 62% (n=93), were females, and 38% (n=57) were males. Learning through WhatsApp was found to be useful by 90% of students. An association (p≤0.02) was found among both genders regarding the usefulness of WhatsApp as an additional learning aid. CONCLUSION: These days, social media is a dominant mechanism used for communal exchanges and is also utilized as an additional aid for teaching and learning purposes. Incorporating social media with conventional class teaching in medical education has evident advantages.